Methionine- and choline-deficient diet enhances adipose lipolysis and leptin release in αP2-Cre fatp4-knockout mice - Cheng, Yuting; Gan-Schreier, Hongying; Seeßle, Jessica; Staffer, Simone; Tuma-Kellner, Sabine; Khnykin, Denis; Stremmel, Wolfgang; Merle, Uta; Herrmann, Thomas; Chamulitrat, Walee (Molecular nutrition & food research, 2020)
Scope Inadequate intake of choline commonly leads to liver diseases. Methionine- and choline-deficient diets (MCDD) induce fatty liver in mice which is partly mediated by triglyceride (TG) lipolysis in white adipose tissues (WATs). Because Fatp4 knockdown has been shown to increase adipocyte lipolysis in vitro, here, the effects of MCDD on WAT lipolysis in aP2-Cre Fatp4-knockout (Fatp4A−/−) mice are determined. Methods and Results Isolated WATs of Fatp4A−/− mice exposed to MCD medium show an increase in lipolysis, and the strongest effect is noted on glycerol release from subcutaneous fat. Fatp4A−/− mice fed with MCDD for 4 weeks show an increase in serum glycerol, TG, and leptin levels associated with the activation of hormone-sensitive lipase in subcutaneous fat. Chow-fed Fatp4A−/− mice also show an increase in serum leptin and very-low-density lipoproteins as well as liver phosphatidylcholine and sphingomyelin levels. Both chow- and MCDD-fed Fatp4A−/− mice show a decrease in serum ketone and WAT sphingomyelin levels which supports a metabolic shift to TG for subsequent WAT lipolysis Conclusions Adipose Fatp4 deficiency leads to TG lipolysis and leptin release, which are exaggerated by MCDD. The data imply hyperlipidemia risk by a low dietary choline intake and gene mutations that increase adipose TG levels.
First published: 29 September 2020
Gesehen am 06.12.2021